Hubungan Antara Beban Kerja dengan Kinerja Petugas Bagian Pelayanan Penunjang Medis di Rumah Sakit PKU Muhammadiyah Sukoharjo - Ananda Nur Khasyanah; Devi Pramita Sari; Puguh Ika Listyorini (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to examine the relationship between workload and performance of medical support staff at PKU Muhammadiyah Sukoharjo Hospital. The healthcare system is constantly growing, and medical support staff play a vital role in ensuring quality care. However, an excessive workload can negatively impact employee performance. This quantitative research employs a cross-sectional approach and includes 76 medical support staff as respondents. The workload was measured using indicators such as job conditions, time usage, and target achievement, while performance was assessed based on work quality, quantity, collaboration, responsibility, and initiative. Data were collected through questionnaires and analyzed using the Kruskal-Wallis statistical test. The findings show that 6.6% of the staff experience a heavy workload, 48.7% a moderate workload, and 44.7% a light workload. In terms of performance, 1.3% have poor performance, 25% moderate, and 73.7% good. The statistical analysis reveals a significant relationship between workload and performance (p-value = 0.001), indicating that higher workloads lead to decreased performance. This study highlights the importance of managing workload effectively to maintain employee performance in medical support services.